Capabilities, opportunities and motivations supporting oral health behaviour of adolescents in Nigerian schools (2019)
Aims: To determine the oral health capabilities, opportunities and motivations supporting oral health behaviour among adolescents in schools in a low-income country. methods: In 2018, this cross- sectional study was conducted among 2097 students in the 10th and 11th grades of 30 randomly selected secondary schools in Ibadan, Nigeria after obtaining ethical approval from the Institution’s Ethics Review Board. Data were obtained with self-administered questionnaires to assess capabilities (oral health knowledge (K), attitude (A) and practices (P)) as well as motivation. A checklist was used to assess availability of oral health promotional activities/materials (opportunities) in the schools concerned. Data were analyzed with SPSS; bivariate analysis was performed using chi square and multivariate analysis with logistic regression. p value for significance was set at 0.05. results: The response rate was 99.5%. Poor oral KAP scores (<50%) were recorded among 2096 ( 99.9%) for K, 1288 ( 61.4%) for A and 1519 (72.4%) for P respectively. There were no oral health promotional materials in any of the schools and the only oral health promotional activity was oral health education in 8 (26.7%) schools; only 331 (15.8%) students had been educated about their oral health. About half 1161 (55.4%) were motivated and will participate in an oral health programme in school. Students; aged 12- 15 years (OR=1.6,95%CI=1.3-1.9, p<0.001), with skilled-worker parents (OR=1.9,95%CI=1.1- 3.3, p=0.020), had received previous oral health education (OR=1.6, 95%CI=1.2-2.0,p<0.001) or had consulted a dentist (OR=2.5,95%CI=1.6-4.0,p= <0.001) had better capabilities. Students who had ≥ 50% final KAP scores (OR=4.7,95%CI=3.3-6.7, p<0.001) had been educated about their oral health (OR =1.7,95%CI=1.1-2.4, p=0.011) were better motivated. conclusions: In the population studied there were gross inadequacies in the oral health capabilities, existing opportunities and motivations for positive oral health behaviour. There were disparities related to socio-demographic characteristics of the students and capabilities, opportunities, motivation influencing oral health behaviour. Oral health capabilities and opportunities were significant predictors of motivation for positive oral health behaviour.